(untitled) (BIRDEM Medical Journal, 2024)
Background: The kidney size of a patient is a valuable diagnostic parameter in clinical practice. Renal size varies with age, gender, body mass index (BMI), pregnancy, race and co-morbid conditions like diabetes mellitus (DM) and hypertension (HTN). Measurements of renal dimensions can be carried out by using different modern techniques like ultrasonography (USG), computed tomography (CT) scan and magnetic resonance imaging (MRI). Out of these modalities USG is choice because of its simplicity, inexpensive, easily available, non-invasive and easy reproducibility. There is no established nomogram for renal size in the Bangladeshi population. Aim of the study was to determine the ultrasonographic renal size in adult Bangladeshi population with no known renal disease and to correlate renal size with age, gender and BMI. In addition, we assess whether hypertension and diabetes mellitus affect renal size. Methods: This cross-sectional study was done in BIRDEM General Hospital and included 55 patients with age >18 years over 6 month period. Study population were not known to have renal disease documented by urine routine microscopy, spot urine for albumin creatinine ratio (ACR), serum creatinine and USG. Their body weight, height and BMI were calculated along with duration of DM and HTN. Analysis was done for differences due to age, gender and laterality. The correlation of renal dimensions with anthropometric parameters were also done. Results: A total of 55 patients were analyzed. There were 19 (34.5%) male and 36 (65.5%) female. The mean age was 46±.10 years. There mean weight, height and BMI were 61 ± 11 kg, 1.54±.069 meter, 25.7 ± 4.8 kg/m2 respectively. In total population 34.5% (19) were diabetic and 32.5% (18) were hypertensive. The means of length, width and parenchymal thickness (PT) of right kidneys (RK) were 10.1 ± 0.87, 4.2 ± 0.67 and 1.4± 0.32 cm respectively. The means of length, width and PT of left kidneys (LK) were 10.3 ± 0.89, 4.5 ± 0.49 and 1.5 ± 0.32 cm respectively. Measurements were significantly higher in LK than those of RK respectively (p=.003, p<.001 and p=.041). There were significant differences in kidney length and PT between sex and age. There were also significant differences in kidney length and PT between subjects of higher BMI, long duration of DM and HTN. The correlation between renal length and weight showed a positive correlation (r = 0.16, p < 0.023). Conclusion: The variation of parameters of both kidneys varies on gender, age, obesity, comorbidity like DM & HTN and with their duration. Length of both kidneys depends on body weight. Further study needed with large samples. BIRDEM Med J 2024; 14(3): 151-157